Phytochemical Screening and Antimicrobial Activity of Piper betle L. and Nicotiana tabacum L. across Dharan, Nepal - Chaudhary, Nitesh Kumar; Chaudhary, Asmita; Shakya, Mejabi; Limbu, Dil K.; Oli, Pramod Sen (Himalayan Journal of Science and Technology, 2023)
Piper betle L. and Nicotiana tabacum L., were studied to find their antibacterial properties. Water, ethanol, methanol, acetone, and petroleum ether were used as solvents for plant crude extraction for phytochemical testings. Total phenolic content and total flavonoid content. Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922) were used as test organisms to determine the antibacterial activity of the plant extracts using agar well diffusion method. This study showed a significant antibacterial activity against both bacterial strains with a zone of inhibition ranging from 7.16 to 17.83 mm for Piper betle L. and 7.16 to 12.5 mm for Nicotiana tabacum L. against Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922). The study reveals that Nicotiana tabacum L. and Piper betle L. can be a promising source against different pathogenic bacteria if thoroughly explored.